Alexa Fluor 546-ArIB[V11L;V16A]is a potent ligand for selectively labeling α7 nicotinic acetylcholine receptors - Hone, Arik J. (2010)
The α7* nicotinic acetylcholine receptor (nAChR) subtype is widely expressed in the vertebrate nervous system and implicated in neuropsychiatric disorders that compromise thought and cognition. In this report, we demonstrate that the recently developed fluorescent ligand Cy3-ArIB[V11L;V16A] labels α7 nAChRs in cultured hippocampal neurons. However, photobleaching of this ligand during long image acquisition times prompted us to develop a new derivative. In photostability studies, this new ligand, Alexa Fluor 546-ArIB[V11L;V16A], was significantly more resistant to bleaching than the Cy3 derivative. The classic α7 ligand α-bungarotoxin binds to α1* and α9* nAChRs. In contrast, Alexa Fluor 546-ArIB[V11L;V16A] potently (IC(50) 1.8 nM) and selectively blocked α7 nAChRs but not α1* or α9* nAChRs expressed in Xenopus oocytes. Selectivity was further confirmed by competition binding studies of native nAChRs in rat brain membranes. The fluorescence properties of Alexa Fluor 546-ArIB[V11L;V16A] were assessed using human embryonic kidney-293 cells stably transfected with nAChRs; labeling was observed on cells expressing α7 but not cells expressing α3β2, α3β4, or α4β2 nAChRs. Further imaging studies demonstrate that Alexa Fluor 546-ArIB[V11L;V16A] labels hippocampal neurons from wild type mice but not from nAChR α7 subunit-null mice. Thus, Alexa Fluor 546-ArIB[V11L;V16A] represents a potent and selective ligand for imaging α7 nAChRs.